2022
DOI: 10.1002/ibra.12062
|View full text |Cite
|
Sign up to set email alerts
|

AQP4 knockout promotes neurite outgrowth via upregulating GAP43 expression in infant rats with hypoxic‐ischemic brain injury

Abstract: Neonatal hypoxic‐ischemic encephalopathy (NHIE) induces severe cerebral damage and neurological dysfunction, with seldom effective therapy. Aquaporin‐4 (AQP4) is involved in aggravating brain damage induced by NHIE. This study aimed to investigate the role of AQP4 underlying the pathogenesis of NHIE. Neonatal Sprague–Dawley rats were used to establish neonatal hypoxic‐ischemic (HI) models, and the expression of AQP4 in the cortex, hippocampus, and lung tissues was detected by real‐time quantitative polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Self‐reparative potential after injury is often associated with factors regulated at the gene and protein levels involving in facilitating neurite outgrowth. 14 , 15 Studies have shown that during normal development of nervous system or regeneration of injured nerves, growth‐associated protein 43 (GAP43) synthesized in growth cones is necessary for the guidance and elongation of growing axons. 16 , 17 Moreover, it also has neuroprotective effects and can regulate the proliferation of neuronal precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐reparative potential after injury is often associated with factors regulated at the gene and protein levels involving in facilitating neurite outgrowth. 14 , 15 Studies have shown that during normal development of nervous system or regeneration of injured nerves, growth‐associated protein 43 (GAP43) synthesized in growth cones is necessary for the guidance and elongation of growing axons. 16 , 17 Moreover, it also has neuroprotective effects and can regulate the proliferation of neuronal precursors.…”
Section: Introductionmentioning
confidence: 99%